How eco-entrepreneurs are transforming Italian tourism sector: Evidence from the hospitality industry - Splendiani, Simone; Testa, Ginevra; Giraldi, Luca; Mencarelli, Chiara (Piccola Impresa / Small Business, 2025)
Purpose. This study investigates eco-entrepreneurship within Italy's hospitality sector, examining the motivations, practices, impacts, and challenges eco-entrepreneurs experience. It aims to enrich the discourse on sustainable tourism and ecological entrepreneurship in Italy. Design/methodology/approach. The research uses a multiple case study methodology to focus on six small-scale enterprises in the Italian hospitality industry. Data collection comprised semi-structured interviews with key informants, supplemented by secondary data analysis. The interviews were coded and analysed using NVivo 14 to extract meaningful insights. Findings. The research reveals that personal commitment, environmental responsibility, and local heritage preservation drive eco-entrepreneurs. Key sustainable practices include resource conservation, waste management, and promoting local products. Transitioning to sustainable operations has been found to enhance reputation and customer trust, although the economic benefits of these initiatives remain unclear. The primary challenges identified are high investment costs, complex regulatory landscapes, and the need for targeted marketing to sensitise consumers towards sustainable options. Practical and Social Implications. The findings highlight potential policy interventions to simplify the certification process and provide economic incentives for eco-friendly practices. Eco-entrepreneurs effectively demonstrate how sustainability in hospitality can engage local communities and influence consumer behaviour towards eco-conscious travel, thereby driving broader societal shifts towards sustainability. Originality of the study. This research contributes to the limited empirical literature on eco-entrepreneurship within Italy's largely small-scale hospitality sector. It underscores the sector's potential to serve as a model for sustainable tourism practices, offering insights that could be applied to other regions and industries.